Projeto ergonômico de assento para tratores, utilizando-se dos recursos da computação gráfica - Deganutti, Roberto [UNESP]; Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP] (My University, 2011)
Regardless its power rate, the tractors are the most used source in operations of tillage. Thus, due to the expansion of cultivated areas and the need of striking application of technologies to meet the advance of agribusiness, it has been shown that these machines are concentrated during the work periods, the physical and mechanical actions to perform the activity. So, it's possible to realize that the time of physical exposures and the operational decision-making are related with the job station comfort. In regard to what was mentioned, this paper's main objective is to design an ergonomically viable seat to furnish the operational requirements of the tractor driver, using the new CAD / CAE technologies in order to provide optimal comfort to the relationship between human being and machines.
Keywords: Tractors; Techonologies CAD/CAE; Design